Penerapan Metode EPQ(Economic Production Quantity) Pada Pengendalian Bahan Baku Laundry Di Samarinda Laundry Mart Barbasis Android - Hanifah Ekawati; Pitrasacha Adytia; Yunita Yunita (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Samarinda Laundry Mart is a business that provides laundry services, besides that it is also a supplier of laundry raw materials in Samarinda. Control of laundry raw materials in the laundry business is a complicated problem. Therefore one method that can be used for raw material control is the EPQ method (Economic Production Quantity) where the EPQ method can determine the optimal production level, optimal production frequency, optimal time cycle to minimize total inventory costs. The results of this study are made inventory control applications using the EPQ method that can make calculations automatically. Only by entering monthly data that is already available. Users can also make transactions using the application so that all data has been integrated in the database to facilitate management in the laundry business. In addition, this application can also print transaction reports and turnover reports.